1980
DOI: 10.1073/pnas.77.10.6211
|View full text |Cite
|
Sign up to set email alerts
|

Avermectin B1a, a paralyzing anthelmintic that affects interneurons and inhibitory motoneurons in Ascaris.

Abstract: ABSIRACrAvermectin B1. (AVM) is an antiparasitic agent that paralyzes nematodes without causing hypercontraction or flaccid paralysis. Using selective stimulation techniques, we have shown that AVM blocks transmission between interneuron(s) and excitatory motoneurons in the ventral nerve cord of Ascaris. It also inhibits transmission between inhibitory motoneurons and muscle but has little effect on excitatory neuromuscular transmission. Picrotoxin can reverse the AVM-induced block of interneuron-excitatory mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 13 publications
(14 reference statements)
5
60
0
2
Order By: Relevance
“…One of the major components of the AVM complex is AVM Bla which has been found to have broad spectrum anthelminthic and insecticidal properties (Egerton et al, 1979;Ostlind et al, 1979). AVM Bla has been shown to block neurotransmission at inhibitory neuromuscular synapses and in the ventral nerve cord ofthe nematode Ascaris suum (Kass et al, 1980). Investigations of AVM at the excitatory neuromuscular junction ofinsects have been restricted to the demonstration that AVM does not affect excitatory postsynaptic potentials in cockroach (Periplaneta americana) muscle (Mellin et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major components of the AVM complex is AVM Bla which has been found to have broad spectrum anthelminthic and insecticidal properties (Egerton et al, 1979;Ostlind et al, 1979). AVM Bla has been shown to block neurotransmission at inhibitory neuromuscular synapses and in the ventral nerve cord ofthe nematode Ascaris suum (Kass et al, 1980). Investigations of AVM at the excitatory neuromuscular junction ofinsects have been restricted to the demonstration that AVM does not affect excitatory postsynaptic potentials in cockroach (Periplaneta americana) muscle (Mellin et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, IVM effects on mf appear only at concentrations far above levels achieved during therapy for filariases (9). In the model nematode Caenorhabditis elegans and intestinal parasitic nematodes, IVM affects pharyngeal pumping and motor activity at concentrations 0.1 to 10 nM (10)(11)(12). Consistent with these effects, glutamate-gated chloride channels (GluCls), the primary nematocidal targets for IVM, are localized in the motor nervous system of these organisms, particularly in motor neuron commissures, lateral and sublateral nerve cords, amphids, and pharyngeal neurons (13).…”
mentioning
confidence: 99%
“…The antiparasitic effects of ivermectin (IVM) are known to be (i) paralysis of the pharyngeal muscle (Geary et al 1993;Martin 1996), and (ii) paralysis of the somatic muscle (Kass et al 1980;Boisvenue et al 1983;Holden-Dye et al 1988;Holden-Dye and Walker 1990). Attempts to elucidate the mode of action of IVM have therefore been focused on the effects of IVM on the neuromuscular system in nematodes.…”
mentioning
confidence: 99%
“…Several lines of evidence have shown that IVM and its analogous avermectins (AVM) interact with GABA receptors (Holden-Dye et al 1988;Martin and Pennington 1989;Holden-Dye and Walker 1990;Ros-Moreno et al 1999), and cause paralysis of the somatic musculature in nematodes (Kass et al 1980;Boisvenue et al 1983). These studies were performed on in situ preparations with unknown subunit composition and the drugs could have acted on multiple receptors.…”
mentioning
confidence: 99%